Incidenca raka v Sloveniji (Incidenca raka v Sloveniji, 1978)
The Cancer Registry of Republic of Slovenia (Registry) is one of the oldest population-based cancer registries in Europe. It was founded in 1950 at the Institute of Oncology in Ljubljana as a special service for collecting and processing data on cancer incidence and cancer patients’ survival. Slovenian Cancer Registry is a voting member of the International Association of Cancer Registries – IACR since its foundation in 1966 as well as a full member of the European Network of Cancer Registries - ENCR since 1990.
Keywords: Rak (medicina); Slovenia; Slovenija; Statistični pregledi